The Effect of Using Decision Support System on Company Benefits at PT Mitra Integrasi Informatika (Case Study on Employees of The IT Deplover Section) - A Djafar, Muhammad Agung; Mahdiana, Deni (Universitas Batanghari Jambi, 2025)
In the era of digitalization, companies are required to operate in tandem with technological developments and are faced with rapid changes in consumption patterns from consumers. One sign of change in the competitive arena is the shift from bureaucratic organizations to organizational forms that are sensitive to vertical, horizontal, and external challenges and opportunities. Companies are currently being helped by the development of management information systems that make it easier to process information into strategic decisions, including the Decision Support System. In organizational benefits, there are three main constructs that may be affected: effective decisions, competitive advantage, and stakeholder satisfaction. Penuli uses the SPSS 23.0 for Windows program in processing data and an analytical framework to evaluate the use of the Decision Support System on company benefits at PT Mitra Integrasi Informatika. Based on the results of the simple linear regression test analysis, the results obtained are the magnitude of the partial relationship of the decision support system. The magnitude of the partial relationship of the decision support system (X) to the benefits of the company (Y) is 5,863 with a p-value of 0.000 <alpha 0.05, stating that Ho is rejected, which means that there is a partial positive influence relationship from the decision support system (X) on company benefits (Y).